Battling the land : 200 years of rural - Linn, Rob. (St. Leonards, N.S.W. : Allen and Unwin, 1999)
The genesis: from the first fleet to 1825. Beyond the boundaries: 1825 to 1850. Reaping adversity: 1850 to 1870. Struggles with Government: 1870 to 1890...
Keywords: Australia; Rural; Country life -- Australia; Rural life -- Australia; Australia -- Rural conditions -- History